The Roles of Hydrazine and Ethylenediamine in Wet Synthesis of Cu Nanowire - Harsojo Harsojo; Lutfi Ayu Puspita; Dedi Mardiansyah; Roto Roto; Kuwat Triyana (Universitas Gadjah Mada, 2017)
A wet synthesis Cu nanowire using CuNO3 as a precursor and hydrazine as a reduction agent and ethylene diamine as a polymer capping agent in excessive sodium hydroxide solution 15 M NaOH has been done. The study was done by varying the volume of hydrazine 0.15, 0.25 and 0.75 mL and ethylenediamine (EDA) (0.5, 1.5 and 0.25 mL) in a total volume of 100 mL, to investigate the roles of these two agents in forming the nanowire and was done at 60 °C at 60 RPM stirring speed. The study revealed that the wet synthesis could be used to produce nanowires in the length of micrometers with a diameter of about hundred nanometers. The best CuNW was obtained at volume EDA 1.5 mL at hydrazine volume 0.15 mL with length to diameter ratio was 120 ± 30. The roles of both hydrazine and the EDA in the process of making nanowires and nanoparticles were also discussed.